2012
DOI: 10.4172/2165-7831.1000112
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Intrauterine Transfusion Therapy: Neonatal Outcomes

Abstract: Background and objectives: Intrauterine blood transfusion (IUT) performed for fetal anemia may be associated with adverse neonatal outcomes. This study aimed to describe the clinical outcome of surviving neonates treated with IUT in an area where detailed outcome on neonatal data is limited. Patients and methods:This prospective study included all living newborns treated with IUT at our institution between March 2004 and February 2011. During this period, 30 newborns with a mean gestation age of 35 weeks (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Several studies showed the incidence of cholestasis in neonatal hemolytic disease to be 13-20% of all patients. 3,4 To our knowledge, for neonates with RHD and cholestatic liver disease, there are only four case reports in the literature that reviewed a specific treatment. [5][6][7][8] This consists of chelation therapy with the usage of intravenous Deferoxamine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed the incidence of cholestasis in neonatal hemolytic disease to be 13-20% of all patients. 3,4 To our knowledge, for neonates with RHD and cholestatic liver disease, there are only four case reports in the literature that reviewed a specific treatment. [5][6][7][8] This consists of chelation therapy with the usage of intravenous Deferoxamine.…”
Section: Discussionmentioning
confidence: 99%
“…Hyporegenerative anemia is a known complication with RHD and IUT. 4,14 Iron supplements with erythropoietin are, therefore, given. However, when iron overload is a concern, like in our case, iron supplement should be discontinued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation